2015
DOI: 10.1177/1367549415585551
|View full text |Cite
|
Sign up to set email alerts
|

‘If you ever saw an Opera singer naked’: The social construction of the singer’s body

Abstract: This article analyzes the process by which a singer's body is turned into an instrument that produces music. Through practice, singers develop bodily habits and a 'corporal memory' consisting of techniques, sensations and positions, all of which are used reflexively when singing. This 'tool kit' enables singers to deconstruct their bodies, mobilizing necessary bodily functions and synchronizing them to meet the requirements of the musical text. Using Bourdieu's concepts of habit and habitus, I illustrate how s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In this, our results concur with social studies of practices (e.g. Bourdieu, 1990Bourdieu, , 2000Gvion, 2015), which suggest that actors 'receive the unspoken social lessons of physical practice' in multiple ways (Prentice, 2007, p. 537). We show that organizational coordination practice, like any other social practice, includes elements that symbolically define actors as practitioners.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this, our results concur with social studies of practices (e.g. Bourdieu, 1990Bourdieu, , 2000Gvion, 2015), which suggest that actors 'receive the unspoken social lessons of physical practice' in multiple ways (Prentice, 2007, p. 537). We show that organizational coordination practice, like any other social practice, includes elements that symbolically define actors as practitioners.…”
Section: Discussionsupporting
confidence: 90%
“…First, they have shown that learning of cultural (Gvion, 2015; O’Connor, 2007), sporting (Müller, 2018; Potter, 2008; Spencer, 2009; Wacquant, 2004), health (Prentice, 2007) or military (Godfrey et al, 2012; Lande, 2007) practices involves bodywork, that is an ‘intensive and finely regulated manipulation of the organism’ (Wacquant, 1995, p. 73) aiming at educating participants and transforming them into practitioners. Second, scholars have also investigated body pedagogics (Shilling, 2017) as the means by which such bodywork is performed.…”
Section: Literature Review: Coordination Practice and Bodyless Actorsmentioning
confidence: 99%
“…Singing lessons are sociocultural spaces, where teachers transmit knowledge and skills. The voice lesson space has been discussed as a setting where habit becomes habitus (Bourdieu, 1977;Gvion, 2016). With changes to the landscape of music education in Ireland, it is pertinent to consider how singing teachers trained within classical institutions teach genres outside of their own embodied habitus.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Western classical singing, through the discipline of classical training and musical canon, conditions vocalisation to the accepted structures defined and dictated by the social and cultural world, referred to by Bourdieu as the field (Bourdieu, 1993). Embodied ways of doing and techniques are adopted by singing bodies (Gvion, 2016), and singers are enculturated to operate within certain social roles and structures which are often reproduced. This pedagogical model enforces codes of behaviour valued by the musical and professional culture to which it belongs, reproducing this culture of vocal behaviour and affirming its status.…”
Section: Negotiating Stylistic Pluralismmentioning
confidence: 99%
“…The Institute’s purpose is to understand the physical habits people need in order to speak in a full and healthy voice, which, they find, includes a relaxed but disciplined full body stance (Gvion, 2016: 156), given that either muscle tension or looseness could deprive a body of the strength required for projection. The visualization of the voice in the MRI is a merging of sound, body, and technological innovations: a new means of preventative medicalization that upholds the conventions of ‘proper articulation’ and a technological witnessing to the intricate structure of muscle tissue.…”
Section: Larynx In the Mirror: The Voice Imagedmentioning
confidence: 99%